2020
DOI: 10.1111/bjet.12904
|View full text |Cite
|
Sign up to set email alerts
|

Semiotics, memory and augmented reality: History education with learner‐generated augmentation

Abstract: has an extensive experience in curriculum design, teaching and training in various contexts and designing research interventions around the investigation of new media literacies. Kenneth edited a book titled "Landscapes of participatory making, modding and hacking: maker culture and makerspaces" which was published in 2017, alongside a second title in 2018, namely "a guide to developing digital games for early grade literacy for developing countries" (the latter commissioned by Digital Learning for Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
1
9
0
2
Order By: Relevance
“…This work is presented as a complement to previous works published in recent times that have shown the effectiveness of augmented reality in education and the processes that comprise it [23][24][25][26][27].…”
Section: Justification and Objectivesmentioning
confidence: 89%
See 1 more Smart Citation
“…This work is presented as a complement to previous works published in recent times that have shown the effectiveness of augmented reality in education and the processes that comprise it [23][24][25][26][27].…”
Section: Justification and Objectivesmentioning
confidence: 89%
“…AR is one of the emerging digital technologies that has aroused the most interest in the educational field [22], because it allows interaction between real and virtual space [23]. This is the fundamental characteristic which defines this type of technology and which differentiates it from virtual reality: the coexistence of both spaces simultaneously [24], which makes it possible to enrich the physical environment by means of the superimposition of virtual information which can appear in different formats and which can be easily activated using mobile devices in some cases [25][26][27].…”
Section: Augmented Reality In Teaching and Learning Processesmentioning
confidence: 99%
“…More recent and pertinent studies regarding learners’ self‐efficacy and conceptions of learning show that the application of AR technology in education can significantly enhance educational effectiveness (Garzón & Acevedo, 2019; Garzón, Pavón, & Baldiris, 2019). AR technology can also visualize the microscopic world such that the students can lively observe the composition of distinct matters (Cai, Wang, & Chiang, 2014); to visualize the abstract concepts in general (Cai et al ., 2017; Dunleavy et al ., 2009); it can even help students memorize factual historical information more effectively (Lim & Lim, 2020). Building on top of the visualization advantages, AR is also powerful in general academic experiences and reformed models of learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies by quantitative empirical investigations of mnemonic strategy have indicated similar positive learning outcomes for students across grade levels, experimental settings, and subject matter content (Balbuena & Buayan, 2014;Maghy, 2015;Mccabe, 2015). Moreover, recent studies interestingly have reported the explicit MoL strategy presented by virtual memory palaces and Augmented Reality (AR) technology (Huynh et al, 2019;Lim & Lim, 2020;Schneider et al, 2020;Vindenes et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 88%